2021
DOI: 10.3390/ijerph18168611
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emotional Behaviour of Spanish, Chilean and England Adolescents, and Their Relationship with Effective Personality

Abstract: Analysing the emotional behaviour of adolescents is fundamental because of its relationship with maladaptive behaviour and even possible psychological maladjustments. For this reason, this study had two objectives: to analyse the existence of significant differences in socio-emotional behaviour in English, Spanish, and Chilean adolescents, taking gender into account, and to analyse the relationship between emotional behaviour and the effective personality model in the Spanish and Chilean samples. A total of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…This is consistent with the previous finding that effective personality helps protect the occupational health of the lecturers through self-efficacy, and satisfaction [ 18 ]. However, this study also shows that effective personality also contributes to the protection and improvement of factor cognitive affections [ 71 ]. In addition, the regression analysis confirms that stronger signs of effective personality have greater positive impacts on factors of self-efficacy, satisfaction, and cognitive affections.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with the previous finding that effective personality helps protect the occupational health of the lecturers through self-efficacy, and satisfaction [ 18 ]. However, this study also shows that effective personality also contributes to the protection and improvement of factor cognitive affections [ 71 ]. In addition, the regression analysis confirms that stronger signs of effective personality have greater positive impacts on factors of self-efficacy, satisfaction, and cognitive affections.…”
Section: Discussionmentioning
confidence: 95%
“…Studies of Healey and Grossman [ 69 ], Rychlak and Slife [ 70 ] show positive correlation between effective personality với cognitive affections. On the other hand, effective personality has negative impacts on exhaustion, musculoskeletal disorders, and voice disturbance in occupational health of lecturers [ 18 , 71 ]. As such, H2 is accepted.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the Effective Personality, Martín del Buey et al [ 27 ] (p. 34) indicated that an effective person is a living being with knowledge of, and esteem for, the self (self-concept and self-esteem); in a process of ongoing maturation (in any state of its evolution); with capacity (intelligence) for achieving (effectiveness) what the person desires (motivation) and hopes to achieve (expectation); using for that purpose the best means (training) possible (efficiency); controlling the causes (attribution of causality) of any achievement (success or failure); confronting personal, circumstantial, and social difficulties (confronting problems) as they may arise; taking balanced decisions with neither detriment to good relations with others (empathy and communication); nor renouncing fair personal aspirations (assertiveness) in their decisions.…”
Section: Introductionmentioning
confidence: 99%